O discurso acadêmico: análise da organização textual-discursivada seção Introdução dos TCC de 2012 do Curso de Pedagogia da Universidade Estadual do Maranhão - Santos, Maria de Fátima Ribeiro dos (Universidade do Vale do Rio dos Sinos, 2015)
Introduction section as an initial part of a TCC (Course Final Assignment) indicates to its reader’s previous information to this study paper. Its aim is a clear and simple formulation of the theme of this research. Due to the restrict studies about TCC (Course Final Assignment), in special about the Introduction section, which is considered one of the compulsory components of an essay in any academic text, it was decided to work on this important section. It is aimed to analyze the compositional organization of the Introduction section in the TCC (Course Final Assignment) from the year 2012 of the Pedagogy Course in UEMA (State University of Maranhão) to verify if the expected segments to the text planning in a TCC (Course Final Assignment) gender have occurred and if there was a link among the textual units. As specific objectives, it was identified the units of the text planning that compose the Introduction section of the TCC (Course Final Assignment) analyzed, considering the units mentioned by Feltrim, Aluísio and Nunes (2000); to examine the role of textual organizations and the role of argumentative connectors as a mark on the segmentation of the stages of the text planning as well as the connection among different parts of the text; to explicit the role of a referential continuity as a mark to a theme continuity. The theory adopted was Discourse Textual Analysis, Adam (2011), mainly about text plan, development of references and argument, ative connectors. It was established relations among, Conte (2013), Koch (2011), Mondada e Dubois (2013) and others. The methodological procedures were done by qualitative approach, exploratory, descriptive and bibliographic research. The corpus of the qualitative analysis was built based on five Introduction sections taken from TCC (Course Final Assignment) investigated. It was started from 36 Introduction sections from which the textual compositions were representative marks of the investigated phenomenon. The results presents a majority number of Introduction sections has shown compositional sequence and compatible text planning to the compulsories and optional stages expected from Feltrin, Aluisio and Nunes (2000),obeying to a conventional structure. Linguistics and discursive operations were a necessary support to the construction of semantic units in the process of a text planning, even though, some gaps were identified (absences, discontinuity), presence of linguistic and textual inexperience of the writers, also connected to some difficulties on recommended directrix to write a scientific text, some occurrences that has not affected the meaningfulness of the text, neither the maintenance of blocks and theme segments responsible for the text planning and for the guarantee of its communicability.
Keywords: TCC; Introdução; Plano de texto; Continuidade; Descontinuidade; Análise textual-discursiva; TCC Course final assignment; Introduction section; Text planning; Continuity; Discontinuity; Discourse textual analysis; ACCNPQ::Lingüística, Letras e Artes::Lingüística